2000
DOI: 10.1002/1099-0739(200007)14:7<355::aid-aoc8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multielement-specific detection of a novel glutathione-arsenic-selenium ion [(GS)2AsSe]? by ICP AES after micellar size- exclusion chromatography

Abstract: In order to confirm the solution structure of [(GS) 2 AsSe] À (GS = glutathione), we have investigated the retention behaviour of a [(GS) 2 AsSe] À /oxidized glutathione (GSSG) mixture on a Sephadex G-25 (SF) column with Tris buffers (0.1 mol dm À3 , pH 8.0) containing various surfactants at concentrations above the critical micellar concentration (CMC): hexadecyltrimethlammonium bromide (HDTAB; 30, 40 and 50 mmol dm À3 ); dodecyltrimethylammonium bromide (DDTAB; 50 mmol dm À3 ); and sodium lauryl sulfate (SLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…The selenoproteins are thought to discharge the nutritional essentiality of Se, the bioavailability of which is a function of its liberation from foods to be metabolized to selenoprotein-bound SeCys. Suboptimal Se status in humans has been associated with increased risk of cancer, and HIV/AIDS and other viral diseases (measles, hepatitis, influenza) including an endemic cardiomyopathy, Keshan Disease, in China (Combs 2001;Gailer et al 2000;Rayman 2002). Supranutritional intakes of Se have been shown to reduce cancer risk (Clark et al 1996), and hundreds of studies with animal tumor models have shown Se to be antitumorigenic through several cellular and metabolic mechanisms (Combs and Lu Junxuan 2001;Combs and Lu 2006;Jackson and Combs 2008).…”
Section: Se-biofortification Of Lentilsmentioning
confidence: 99%
“…The selenoproteins are thought to discharge the nutritional essentiality of Se, the bioavailability of which is a function of its liberation from foods to be metabolized to selenoprotein-bound SeCys. Suboptimal Se status in humans has been associated with increased risk of cancer, and HIV/AIDS and other viral diseases (measles, hepatitis, influenza) including an endemic cardiomyopathy, Keshan Disease, in China (Combs 2001;Gailer et al 2000;Rayman 2002). Supranutritional intakes of Se have been shown to reduce cancer risk (Clark et al 1996), and hundreds of studies with animal tumor models have shown Se to be antitumorigenic through several cellular and metabolic mechanisms (Combs and Lu Junxuan 2001;Combs and Lu 2006;Jackson and Combs 2008).…”
Section: Se-biofortification Of Lentilsmentioning
confidence: 99%
“…We have shown that this species is formed in vivo and subsequently excreted in bile (12)(13)(14). [(GS) 2 AsSe] -therefore represents a fundamental molecular link between the metabolism of arsenite and selenite in mammals and thus is of considerable toxicological importance (12).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the latter retention strategy would most likely also minimize a possible decomposition of [(CH 3 ) 2 As(Se) 2 ] − during the chromatographic separation process, as was previously observed with the structurally related species [(GS) 2 AsSe] − on anion-exchange columns. 6 Since the ultimate goal was to develop a chromatographic method for the identification of [(CH 3 ) 2 As(Se) 2 ] − in biological samples, PBS buffers (0.01 mol dm −3 ) were investigated as mobile phases (the utilization of other mobile phases could lead to the decomposition of [(CH 3 ) 2 As(Se) 2 ] − on the chromatographic system). The decomposition of [(CH 3 ) 2 As(Se) 2 ] − below pH 7.0, however, required a mobile phase with pH > 7.0.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 The simultaneous exposure of the general population to dimethylarsinate and dietary selenium compounds could, therefore, lead to the in vivo formation of [(CH 3 ) 2 As(Se) 2 During the development of an SEC-ICP-AES method for the identification of [(GS) 2 AsSe] − in aqueous solutions, we previously noticed that the stationary phase must be chosen carefully in order to prevent the decomposition of this species during the chromatographic separation. 6 In view of these findings, and with regard to the similar chemical properties of [(GS) 2 AsSe] − and [(CH 3 ) 2 As(Se) 2 ] − (both are oxygen sensitive and decompose below pH 7.0), 6,10 the development of an HPLC method for the identification of [(CH 3 ) 2 As(Se) 2 ] − requires that this species can be passed through the stationary phase unchanged and structurally intact. [(CH 3 ) 2 As(Se) 2 ] − contains two As-C and two As-Se single bonds.…”
Section: Introductionmentioning
confidence: 99%